Characterization and Comparison of Bacterial Communities of an Invasive and Two Native Caribbean Seagrass Species Sheds Light on the Possible Influence of the Microbiome on Invasive Mechanisms - Aires, Tania; Stuij, Tamara M.; Muyzer, Gerard; Serrão, Ester A.; Engelen, Aschwin H. (Frontiers in Microbiology, 2021)
Invasive plants, including marine macrophytes, have been one of the most important threats to biodiversity. Invasion success is dependent on interactions among living organisms, but when studying it the possible positive interactions are mostly under looked. Recent studies suggested that microorganisms associated with eukaryotic hosts may play a determinant role in the invasion process. Along with the knowledge of their structure, taxonomic composition and potential functional profile, understanding how bacterial communities are associated with the invasive species and the threatened natives (species-specific/environmentally shaped/tissue-specific), can give us a holistic insight into the invasion mechanisms. Here we aimed to compare the bacterial communities associated to leaves and roots of two native Caribbean seagrasses (Halodule wrightii and Thalassia testudinum) with those of the successful invader Halophila stipulacea using 16S rRNA gene amplicon sequencing and predicting their functional profile, around the Caribbean island Curaçao. Invasive microbiomes were more diverse and included three times more species-specific core OTUs than the natives. Associated bacterial communities were seagrass-specific, with higher similarities between natives than between invasive and native seagrasses for both communities associated with leaves and roots, despite their strong tissue differentiation. However, with a higher number of OTUs in common, the core community of the native H. wrightii was more similar to that of the invader H. stipulacea than T. testudinum. The invasive H. stipulacea was enriched in halotolerant bacterial genera with plant growth-promoting properties and other potential beneficial effects for hosts. Predicted functional profiles also revealed some advantageous traits on the invasive species as detoxification pathways, protection against pathogens and stress tolerance. We demonstrated that the bacterial community associated with the invasive seagrass H. stipulacea is different from native seagrasses, including some potentially beneficial bacteria, suggesting the importance of considering the microbiome dynamics as a possible and important influencing factor in the adaptability of non-indigenous species. We suggest further comparison of H. stipulacea microbiome from its native range with that from both the Mediterranean and Caribbean habitats with a contrasting invasion success. Also, combining meta-omics with bacterial manipulation experiments would confirm possible functional advantage in the microbiome of this invasive seagrass.